2004
DOI: 10.1002/mrc.1527
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of poly(diethylsiloxane) in the crystalline, liquid crystalline and isotropic phases by solid‐state 17O NMR spectroscopy and ab initio MO calculations

Abstract: The structure of poly(diethylsiloxane) (PDES) has been characterized using solid-state NMR of (17)O. The sample studied had a weight-average molecular weight of 2.45 x 10(5). The sample was prepared by utilizing the cationic ring-opening polymerization of (17)O-enriched hexacyclotrisiloxane. Solid-state NMR of (17)O-enriched PDES was measured on the low-temperature beta(1) phase, the high-temperature beta(2) phase, the two-phase system consisting of the liquid crystal and isotropic liquid phase and the isotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…A number of recent solid-state 17 O NMR studies have accumulated a considerable amount of experimental data on the tensorial aspect of the 17 O NMR parameters. [2][3][4][5][6][7][8][9][10][11][12][13][14] In parallel to experimental studies, attention has also been paid to theoretical prediction of 17 O NMR tensors. 12,13,[15][16][17][18][19][20] The purpose of performing first-principle calculations on 17 O NMR tensors is not only to check the validity of computational methodology, but also to provide a useful tool for interpreting experimental NMR data in relation to HB interaction, molecular structure, and dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent solid-state 17 O NMR studies have accumulated a considerable amount of experimental data on the tensorial aspect of the 17 O NMR parameters. [2][3][4][5][6][7][8][9][10][11][12][13][14] In parallel to experimental studies, attention has also been paid to theoretical prediction of 17 O NMR tensors. 12,13,[15][16][17][18][19][20] The purpose of performing first-principle calculations on 17 O NMR tensors is not only to check the validity of computational methodology, but also to provide a useful tool for interpreting experimental NMR data in relation to HB interaction, molecular structure, and dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…We thank Dr. Hartmut Schmider of HPCVL for technical assistance. R.I. is grateful to Queen's University for an R. S. McLaughlin Fellowship (2004-2005. We also thank Ms. Kathy Xu for assistance in preparing the manuscript.…”
mentioning
confidence: 96%
“…CO 2 dynamics in MOFs are typically studied via 13 C solid-state NMR (SSNMR) experiments using 13 C-enriched 13 CO 2 gas. 13 C is a spin-1/2 nucleus associated with relatively narrow static SSNMR powder patterns that exhibit lineshapes dominated by the anisotropic chemical shift (CS) interaction, which is sensitive to the local environment and dynamics. 17 O SSNMR experiments are often used for characterization of oxides, glasses, and biomolecules. 17 O SSNMR experiments are also a sensitive probe of dynamics, but are rarely used for this purpose. 17 O has a spin of 5/2, a nuclear quadrupole moment of −25.6 mb, and a low natural abundance (0.037%) that usually requires isotopic enrichment. The quadrupolar interaction (QI) with the local electric field gradient (EFG) often gives rise to broad SSNMR spectra of low signal-to-noise ratios (S/N) that demand long experimental times; however, the QI is also sensitive to local structure and dynamics.…”
mentioning
confidence: 99%
“…564 Structural characterisation of poly(dimethylsiloxane) was achieved using 17 O MAS NMR spectroscopy. 565 1 H and 29 Si NMR data were used to determine the structure of a poly(dimethylsiloxane) layer at the surface of hydrophilic SiO 2 . 566 29 Si CP/MAS NMR spectra were used to characterise poly(aminopropyl/phenyl)silsesquioxane.…”
Section: Aluminiummentioning
confidence: 99%
“…829 Solid-state 17 O NMR data probed the structure and dynamics of poly(diethylsiloxane) in b 1 and b 2 liquid crystal phases. 830 Solid-state 2 H NMR spectra were used to determine the motion of NH 4 + ions in feldspar, N(D/H) 4 AlSi 3 O 8 . 831 A 31 P NMR study has been reported for spin-dynamics in Si:P. 832 1 H and 31 P spin pairs in solid SnHPO 3 and SnHPO 4 gave information on spindynamics in these systems.…”
Section: Motion In Solidsmentioning
confidence: 99%